Determining the factors for interhospital transfer in advanced heart failure cases. (June 2022) - Narita, Koichi; Amiya, Eisuke; Hatano, Masaru; Ishida, Junichi; Minatsuki, Shun; Tsuji, Masaki; Bujo, Chie; Kakuda, Nobutaka; Isotani, Yoshitaka; Ono, Minoru; Komuro, Issei
Abstract: Background: There are some patients with advanced heart failure (HF), for whom implantable left ventricular assist device (LVAD) or heart transplantation (HTx) should be considered. Some of them need to be transferred between hospitals. There are few reports on the interhospital transfer of patients with advanced HF and their subsequent clinical course. In this study, we investigated the characteristics and clinical course of patients transferred to a LVAD/HTx center, focusing on the distance between hospitals. Methods: We retrospectively examined 141 patients who were transferred to our hospital, considering the indications of LVAD implantation or HTx. We divided the patients into two groups: those referred <33 km (short-distance) and those referred more than 33 km (long-distance). The primary outcome was the composite outcome of increased catecholamine dose, mechanical support, or renal dysfunction within 1 week of transfer. Results: Continuous catecholamine infusion was significantly more common in patients in the long-distance group, whereas extracorporeal membrane oxygenation (ECMO) placement was significantly more common in short-distance group. Patients transferred via long distance had significantly higher rates of increased catecholamine doses, mechanical support including intra-aortic balloon pumping (IABP) and ECMO, and renal dysfunction within 1 week of transfer than patients transferred via short distance. Multivariate analysis showed that low body mass index (BMI) and long distance were independent predictive factors for the primary outcome. Conclusions: When patients with advanced HF are transferred from far distant hospitals or with low BMI, it may be necessary to devise various measures for interhospital transport.